Will shared leadership engenders innovative work behaviors among salesmen toward improved performance? - Oniku Ayodele; Mokwenyei Anita Kehinde (International Journal of Management and Economics, 2020)
Studies have shown that issue of shared leadership is directly related to leadership style adopted in the organization, which is germane and strategic to teamwork to effectuate high business performance across industries. The study looks at the relationship between the different leadership styles and innovative work behaviors (IWBs) that would ultimately lead to improved performance in financial sector among sales team. Thus, the study examines the operational frameworks of the different leadership styles and the effects on IWBs vis-à-vis sales team work in the financial industry. The case of financial industry stems from the fact that operations are currently changing from arm-chair marketing to aggressive selling strategy to improve customer base and financial inclusion in the economy. The study found out that leadership styles- transformational leadership, individual empowering leadership (IEL), team empowering leadership, and participative leadership (PL) are very strategic to sales teamwork, but IEL and PL are more strategic and performance-enhancing to behaviorIWB in financial sector sales teamwork.
Keywords: M3; 650; shared leadership; transformational leadership; individual empowering leadership; team empowering leadership; participative leadership; innovative work behavior; sales force